RELATION BETWEEN EVENT HYPERTENSION WITH WORRIED OF ELDER-AGE-PERSON (Studies On Posyandu Jabaran, Kedungpari Village, Sub-District Mojowarno Jombang - Deviana Nur Faizah; Marxis Udaya; Inayatur Rosyidah (STIKES Insan Cendekia Medika Jombang, 2011)
Hypertension disease is the most disease that suffered by Indonesian People that can happen caused by one of the problems that often appear from change of life-style. Hypertension is negative impact to physic and also physiology of elder-age-person. Worried is one of uncomfortable reactions to this disease because it is not effective mechanism coping individual. Based on study before, 7 from 10 elder-age-persons said that they felt worried with hypertension they felt. The purpose of this research is to analyze the relation event hypertension with worried of elder-age-person in elder-age-person Posyandu Jabaran Sub-Village, Kedungpari Village, Sub-District Mojowarno, District Jombang The research method, Annalistic Cross Sectional. Populations of this research is all elder-age-person in Posyandu in Jabaran Sub-Village as many as 35. Sampling Technique is Total Sampling. Variable in this research is hypertension event as independent variable and elder-age-person’s worried as dependent variable. Gaining data of this research by using instrument of questionnaire. Analyzing data method, by using editing, coding, scoring, tabulating and to test statistic using spearman rank test.Result of this research from 35 respondents almost half of the respondents having light hypertension as many as 14 respondents (40%) and 12 respondents (34%) having medium hypertension also 9 respondents (26%) having heavy hypertension. For worried variable, most of the respondents are having heavy worried as many as 20 respondents (57%) and 15 respondents (43%) are having medium worried. Spearman rank test from variable gained value ρ= 0,001 and α=0,05 it means ρ<α that has mean H1 is accepted. Conclusion from the research is there a relation between event hypertension with worried of elder-age-person.